IMPLEMENTASI SENSOR MONITORING PADA JARINGAN WI-FI (HOTSPOT) BERBASIS SNORT - Ahmad Faisol; Imam Izzat Muttaqin (Jurnal Teknologi Informasi dan Terapan, 2019)
The wireless networking application besides giving the simplicity in communication or data exchange, also has a weakness in security system. Every user's tools that connected to the wireless network must be ready towards the appearance of the destruction or attack, because wireless network doesn't have a clear defense track. On this research, monitoring sensor application based on Snort is being suggested as one of the solutions that can be used to help the network arrangement in monitoring the condition of the network and analyze every dangerous package that is in the network. Snort will detect the intruder and analyze the package that cross the network directly and recording into the data storage media. Monitoring sensor is using rule-base system that will detect every package based on the directions that has defined to the direction data collection. The result of the research shown every new data package that entry the sensor, so the change of the event's amount of the monitoring sensor will change automatically based on the admin's arrangements. More data that cross the sensor, can influence the activity from the server that shown by the slow response from the web server.